2021
DOI: 10.1371/journal.pone.0253641
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of duloxetine compared with opioid for postoperative pain control following total knee arthroplasty

Abstract: Background The purpose of this study was to assess the efficacy of duloxetine as an alternative to opioid treatment for postoperative pain management following total knee arthroplasty (TKA). Methods Among 944 patients, 290 (30.7%) of patients received opioid or duloxetine for pain control for 6 weeks when the pain Visual Analogue Scale (VAS) score was greater than 4 out of 10 at the time of discharge. 121 patients in the Opioid group and 118 in the Duloxetine group were followed up for more than one year. Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 41 publications
(87 reference statements)
0
29
0
Order By: Relevance
“…In addition, the title list was imported into Endnote software, 152 studies which was duplicated or did not meet the inclusion criteria such as reviews, meta-analysis, animal-based studies, case report, and conference papers were excluded. After referring to the full text, 1 retrospective trial and 2 protocols were excluded, and 8 randomized controlled trial (RCT) [11,12,[18][19][20]24,29,30] with 739 patients were finally included. The study selection process and reasons for exclusion are summarized in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the title list was imported into Endnote software, 152 studies which was duplicated or did not meet the inclusion criteria such as reviews, meta-analysis, animal-based studies, case report, and conference papers were excluded. After referring to the full text, 1 retrospective trial and 2 protocols were excluded, and 8 randomized controlled trial (RCT) [11,12,[18][19][20]24,29,30] with 739 patients were finally included. The study selection process and reasons for exclusion are summarized in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Eight RCTs [11,12,[18][19][20]24,29,30] reported the method of randomization, with 7 [11,[18][19][20]24,29,30] randomized through computer-generated lists and 1 [12] through random number table. Blinding was maintained using sealed envelopes in 8 studies, and 6 [18][19][20]24,29,30] reported blinding of the operator and participants, and 2 [11,12] reported blinding of the patients, the treating physicians and the statisticians. No study showed an unclear bias due to incomplete outcome data or selective outcome reporting.…”
Section: Quality Assessment and Basic Informationmentioning
confidence: 99%
See 3 more Smart Citations